Modern Methods of Histological Examination - Sobirova Dildora Ravshanovna; Azizova Feruza Khusanovna; Otajonova Aziza Nigmatullayevna; Surayyo Habibullayevna Ishandzhanova,; Tursunmetov Ibodulla Roziboyevich,; Makhmudova Shakhlo Ismatullayevna (Zien Journals, 2023)
This article provides information about histology, the most modern methods of histological examination that are being tested and used in the current age of technology.
Keywords: histology; histological examinations; tissues; cells